PERPADUAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING DENGAN COURES REVIEW HORAY DALAM MENINGKATKAN HASIL BELAJAR SISWA SMP NEGERI 7 AMBON - Reni S YangLera; J F Rehena; P M. J Tuapattinaya (Program Studi Pendidikan Biologi FKIP Unpatti, 2020)
Background: In an effort to improve Biology learning outcomes at school, teachers need to apply learning models that enable students to achieve these needs. One learning model used by researchers is the Student Facilitator and Explaining learning model combined with the Coures Review Horay model. Student Facilitator and Explaining makes students as facilitators, namely providing opportunities for students to explain or convey ideas to other students. While Coures Review Horay asks students to write answers to questions on a given card that has a number. Method: This research includes descriptive research and analysis used to determine the effectiveness of the application of the model using manual analysis. The data source in this study was students of class VIII-1 SMP Negeri 7 Ambon with a total of 30 students. Results: The application of the Student Facilitator And Explaining learning model combined with the Course Review Horay model can improve the learning outcomes of the Human Digestive System material in Grade VIII students of SMP Negeri 7 Ambon. This result is seen in the average value obtained at the final value of 79.70. Conclusion: There are differences in learning outcomes before and after the implementation of the Student Facilitator and Explaining learning model combined with the Coures Review Horay model in the Human Digestive System material.